Nutrition Problems of the Urban Family - Macapinlac, Manuel (Science Diliman: A Journal of Pure and Applied Sciences; Vol 1 (1980), 2007)
During the recent years, there has been a surge of interest in the nutritional metabolic role of the "trace" mineral elements. Part of this interest is due to improved case in the quantitative analyses of these elements by the introduction of atomic absorption spectrophotometry. However, it has been the studies on zinc, in particular, that have fueled much of this interest when it was discovered that naturally-occurring zinc-deficiency could happen in man. It was reported that a syndrome consisting of dwarfism, iron-deficiency, anemia hepato-splenomegaly occurs in poor viIlages in Egypt and Iran. This syndrome was accompanied by low plasma and hair zinc levels, and decreased urinary excretion of zinc. Prior to this report, it has been tacitly assumed that since many of the "trace" elements occur in fairly abundant quantities in food, and because they are present in very small quantities in the tissues of man, dietary deficiency of the trace minerals was unlikely to occur in man. It has become obvious that difficulty in absorption or poor availability of the trace elements from the diet may prove to be an important etiologic mechanism in the causation of deficiencies of these elements. In the case of zinc, a study in the United States reported cases of children with low hair zinc concentration and with low taste acuity (hypogeusia). The condition responded to treatment with zinc supplementation. It was also reported that zinc-deficiency is secondary to intestinal malabsorption. The possibility that zinc-deficiency might accompany protein-calorie malnutritions had been suggested by some investigators who found low plasma zinc levels in children with kwashiorkor. Since protein-calorie malnutrition is a world-wide problem and is particularly common in developing countries, it appears important that in the nutrition research programs of such countries. In this study made on apparently normal adults, the zinc levels in serum and hair were examined. Current studies made on pregnant women will be the subject of a subsequent report.